41.6k views
0 votes
John is listing each step of the equation +4 = 10 – 3 폼 5+4= 10 - 3 *5 = +4= 7 c+4= -35 TE -39 What was his mistake?

John is listing each step of the equation +4 = 10 – 3 폼 5+4= 10 - 3 *5 = +4= 7 c+4= -35 TE-example-1
User Sehrope
by
3.9k points

1 Answer

3 votes

Answer:

x+ 4= -35

Step-by-step explanation:

Given the equation:


(x)/(-5)+4=10-3

The next step is:


(x)/(-5)+4=7

The next step should have been:


\begin{gathered} (x)/(-5)=7-4 \\ (x)/(-5)=3 \end{gathered}

Therefore, his mistake was the step below:


x+4=-35

User JonMinton
by
5.1k points